(untitled) (Journal of Pathology of Nepal, 2014)
Non Hodgkin lymphoma with infarction at initial presentation is rare and can be confused with an acute inflammatory process. A 47 year-old-man presented with complaint of swelling in the left parotid region for 2 weeks which increased in size with severe, continuous and throbbing pain in the last 2-3 days. A clinical diagnosis of parotid abscess was made. Incision and drainage did not yield any pus. Fine needle aspiration cytology showed a highly cellular tumor comprising of somewhat uniform round cells with granular nuclear chromatin. Ghost outline of cytoplasm was noted. A diagnosis of infarcted neoplasm of the parotid gland, probably acinic cell carcinoma was suggested. Histopathologically, it was reported as non-Hodgkin lymphoma with infarction which was confirmed by immunohistochemistry. DOI: http://dx.doi.org/10.3126/jpn.v4i7.10319 Journal of Pathology of Nepal (2014) Vol. 4, 591-593